Ameliorative effects of the ethanolic extract of Allium saralicum R.M. Fritsch on CCl4-induced nephrotoxicity in mice: A stereological examination - Sherkatolabbasieh, Hamidreza; Hagh-Nazari, Lida; Shafiezadeh, Shiva; Goodarzi, Nader; Zangeneh, Mohammad Mehdi; Zangeneh, Akram (Archives of Biological Sciences, 2017)
The present study was carried out to investigate the nephroprotective effect of the ethanolic extract of Allium saralicum R.M. Fritsch (ASRMF) in mice. Thirty-five male mice were divided into five groups (n=7). Group 1 (positive control) received 1 mL/kg olive oil intraperitoneally (i.p.) and 0.5 mL distilled water orally; Group 2 (negative control) received CCl4 (50% in olive oil, 1 mg/kg; i.p.); Groups 3, 4 and 5 received CCl4 and 200, 800 and 1600 µg/kg of ASRMF extract, respectively. The renal volume and cortex in Groups 1 and 2 were increased by 55% and 62% (p≤0.001) following CCl4 administration, respectively, and were improved after ASRMF administration. The volume of proximal convoluted tubules (PCTs), glomeruli, vessels and interstitial tissue increased 80%, 150%, 83% and 64% (p≤0.05), respectively, in CCl4-treated mice, and decreased significantly with 800 and 1600 µg/kg of ASRMF. The length of PCTs and vessels increased 51% and 45% and decreased (p≤0.05) with 200, 800 and 1600 µg/kg of ASRMF, respectively. CCl4-treated mice lost 22.5% of glomeruli; the loss was inhibited significantly (p≤0.05) by ASRMF. Urea and creatinine concentrations were increased (p≤0.05) in CCl4-induced nephrotoxicity as compared to the controls, whereas different doses of ASRMF restored the levels of these biomarkers compared to the negative controls. In conclusion, ASRMF has a potent nephroprotective property and can improve renal structural and serum biomarkers in CCl4-induced nephrotoxicity in mice. https://doi.org/10.2298/ABS160914129S Received: September 14, 2016; Revised: November 18, 2016; Accepted: November 21, 2016; Published online: November 28, 2016 How to cite: Sherkatolabbasieh H, Hagh-Nazari L, Shafiezadeh S, Goodarzi N, Zangeneh MM, Zangeneh A. Ameliorative effects of the ethanolic extract of Allium saralicum R.M. Fritsch on CCl4-induced nephrotoxicity in mice: A stereological examination. Arch Biol Sci. 2017;69(3):535-43.